2014
DOI: 10.7448/ias.17.1.18822
|View full text |Cite
|
Sign up to set email alerts
|

Spending of HIV resources in Asia and Eastern Europe: systematic review reveals the need to shift funding allocations towards priority populations

Abstract: IntroductionIt is increasingly important to prioritize the most cost-effective HIV interventions. We sought to summarize the evidence on which types of interventions provide the best value for money in regions with concentrated HIV epidemics.MethodsWe conducted a systematic review of peer-reviewed and grey literature reporting measurements of cost-effectiveness or cost-benefit for HIV/AIDS interventions in Asia and Eastern Europe. We also collated HIV/AIDS spending assessment data from case-study countries in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…A recent study on population-level cost-effectiveness of the large community-based Avahan programme in south India strongly indicated that KAP-focused interventions are highly cost-effective [ 44 ]. Our findings recommend a shift of available resources away from the general populations and towards the KAPs in Vietnam, which is consistent with a recent systematic review of HIV funding landscape in other Asian settings [ 45 ]. NSPs and condom programmes amongst MSM and FSW/clients should be specifically prioritised.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study on population-level cost-effectiveness of the large community-based Avahan programme in south India strongly indicated that KAP-focused interventions are highly cost-effective [ 44 ]. Our findings recommend a shift of available resources away from the general populations and towards the KAPs in Vietnam, which is consistent with a recent systematic review of HIV funding landscape in other Asian settings [ 45 ]. NSPs and condom programmes amongst MSM and FSW/clients should be specifically prioritised.…”
Section: Discussionsupporting
confidence: 91%
“…Many HIV epidemics in the last decade are concentrated among MARPs, specifically people who inject drugs, sex workers and men who have sex with men [36-38]. The preponderance of HIV spending in most countries with concentrated epidemics remain targeted to the general population [39], despite evidence of the effectiveness and low cost of prevention and treatment programs targeting MARPs.…”
Section: Introductionmentioning
confidence: 99%
“…The average fungibility of aid for HIV has not been well established, with various publications reporting conflicting messages [ 13 , 14 ]. Competing domestic budgetary priorities across the health sector and political agendas mean that domestic resources will not automatically replace declining ODA [ 6 , 15 ]. This issue is an open question into which further research would be very welcome.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, prevention programmes for people most at risk of acquiring HIV are almost entirely funded from international sources. Domestically funded prevention programmes are all too often non-targeted or targeted at general lower risk populations [ 15 ]. With all of the accumulated knowledge and evidence, and especially considering the future financing landscape, domestically funded HIV programmes need to deliver effective prevention strategies that focus on key populations and are designed to respond to local conditions and epidemiology.…”
Section: Discussionmentioning
confidence: 99%